THE MISSING PIECE TO TEACHER INDUCTION: A FRAMEWORK FOR ADDING EQUITY-FOCUSED SUPPORT TO INDUCTION - Lassiter, John Russell (East Carolina University, 2023)
Teacher turnover rates in the nation are incredibly high, and college of education programs are experiencing declining enrollment. Combined, these two factors have led to staffing concerns in most states. A lack of highly qualified teachers threatens the quality of education historically hard-to-staff schools can provide their students. The first few years of teaching are vitally important to an educator's long-term success. Reimagining teacher induction is needed to help new teachers find success and overcome the pressures of teaching early in their career. A site-based induction process layered on top of traditional district induction can help new staff uncover their beliefs about teaching and learning while supporting the development of culturally responsive teaching methods. This layered support is a higher level of support beyond what the district can provide on its own. This qualitative research study uses participatory action research (PAR) informed by the principles of improvement science and Community Learning Exchange (CLE) axioms to engage a Co-Practitioner Researcher (CPR) team in building a site-based, equity-focused induction process that combines site-based support with the state-required district induction program. The findings of (1) communal learning space and (2) evolve to involve can help hard-to-staff schools in similar contexts support new teachers in reexamining long-held beliefs about teaching and learning while developing an understanding of the importance of culturally responsive teaching practices in schools. The study outlines practices used to establish a communal learning space where a Teacher Alliance Group (TAG) aids new teachers in improving their professional practices as all teachers gain knowledge of what it means to be a culturally responsive educator.
Keywords: Reimagining Teacher Induction; Offering Equity Support; Community Learning Exchange; Teacher orientation; Culturally relevant pedagogy; Teacher turnover--Prevention